Freqüência de anquiloglossia em uma comunidade indígena brasileira - Vieira, Evanice Marçal [UNESP]; Hespanhol, Daniele; Salineiro, Fernanda Cristina Sales; Jardim Júnior, Elerson Gaetti [UNESP] (My University, 2010)
Objective: This study aimed to assess the prevalence of ankyloglossia in people of different age groups living in the native Brazilian community of Umutina, in the municipality of Barra do Bugres/Mato Grosso. Methods: The sample consisted of 291 native Brazilians who underwent clinical examination. Results: Ankyloglossia was observed in 108 (37.11%) individuals. There was a greater prevalence of ankyloglossia among males, with 57 cases (43.8%) against 51 cases (31.7%) in females. Age distribution was done after analyzing the hierarchical grouping, resulting in three age groups: 1- to 20-year-olds, 21- to 45-year-olds and 46- to 99-year-olds. Ankyloglossia was more prevalent in the youngest group, with 65 cases (40.6%). Conclusion: Although there is a high rate of ankyloglossia among the individuals who live in the Umutina Reservation, ankyloglossia does not seem responsible for the changes associated with phonation, mastication, presence of diastema and periodontal problems, since these changes were infrequent and generated no complaints.

Objetivo: Avaliar a prevalência de anquiloglossia na comunidade indígena Umutina, no município de Barra do Bugres (MT), em diversas faixas etárias. Métodos: A amostra foi constituída de 291 índios que se submeteram ao exame clínico. Resultados: A anquiloglossia foi observada em 108 (37,11%) índios. O sexo masculino apresentou maior prevalência, sendo 57 casos (43,8%), enquanto o sexo feminino apresentou 51(31,7%) dos casos. A distribuição da faixa etária foi feita após análise de agrupamento hierárquico, distribuídas em três grupos: 1-20 anos, 21-45 anos e 46-99 anos. Sendo que a anquiloglossia apresentou maior prevalência na faixa etária de 1- 20 anos, com 65 casos (40,6%). Conclusão: Verificou-se que, apesar da anquiloglossia se apresentar nas etnias da reserva indígena Umutina com frequência elevada, a mesma não parece ser responsável por alterações associadas à fonação, mastigação, presença de diastema e problemas periodontais, uma vez que essas alterações foram observadas em baixa frequência e não foram motivos de queixas da população.
Frequency of ankyloglossia in a community of native Brazilians
Keywords: Lingual frenum; Tongue; Indigenous population; Freio lingual; Língua; População indígena